Photodynamic inactivation of bioluminescent Escherichia coli by neutral and cationic pyrrolidine-fused chlorins and isobacteriochlorins - Mesquita, Mariana Q.
Photodynamic inactivation of bioluminescent Escherichia coli in the presence of cationic chlorin and isobacteriochlorin photosensitizers (PSs) obtained from 5,10,15,20-tetrakis(pentafluorophenyl)-porphyrin is described. The spectroscopic data for the neutral and cationic derivatives and their photophysical characterizations, especially fluorescence and singlet oxygen generation capacity are also reported. The results show that there is a direct relation between the inactivation efficiency and the increasing number of charges on the molecules. The combined effect of higher wavelength absorption and number of positive charges on the PS shows a 6.1 log reduction during the inactivation process. Overall this study shows that the cationic isobacteriochlorin has high potential to be used as PS for the inactivation of Gram (-) bacteria.